Smoking among pregnant women in Cantabria (Spain): trend and determinants of smoking cessation - Mariscal Marcial; Llorca Javier; Pardo-Crespo Rosa; Pérez-Iglesias Rocio; Palma Silvia; Delgado-Rodríguez Miguel (BMC, 2007)
Abstract Background Cantabria (Spain) has one of the highest prevalence of smoking among women of the European Union. The objectives are to assess the trend of smoking during pregnancy in a five-year period and the determinants of smoking cessation during pregnancy in Cantabria. Methods A 1/6 random sample of all women delivering at the reference hospital of the region for the period 1998-2002 was drawn, 1559 women. Information was obtained from personal interview, clinical chart, and prenatal care records. In the analysis relative risks and 95% confidence intervals were estimated. Multivariable analysis was carried out using stepwise logistic regression. Results Smoking prior to pregnancy decreased from 53.6% in 1998 to 39.4% in 2002. A decrease in smoking cessation among women smoking at the beginning of pregnancy was observed, from 37.3% in 1998 to 20.6% in 2002. The mean number of cigarettes/day (cig/d) before pregnancy remained constant, around 16 cig/d, whereas a slight trend to increase over time was seen, from 7.7 to 8.9 cig/d. In univariate analysis two variables favoured significantly smoking cessation, although they were not included in the stepwise logistic regression analysis, a higher education level and to be married. The logistic regression model included five significant predictors (also significant in univariate analysis): intensity of smoking, number of previous pregnancies, partner's smoking status, calendar year of study period (these four variables favoured smoking continuation), and adequate prenatal care (which increased smoking cessation). Conclusion The frequency of smoking among pregnant women is very high in Cantabria. As smoking cessation rate has decreased over time, a change in prenatal care programme on smoking counseling is needed. Several determinants of smoking cessation, such as smoking before pregnancy and partner's smoking, should be also addressed by community programmes.